Diversity and composition of invasive understory plants in Kapalo Banda Taram Ecotourism Area, West Sumatra, Indonesia - DEWI NURHASANAH; SOLFIYENI SOLFIYENI; HAFIZUL MAULANA MUFTI; TESRI MAIDELIZA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nurhasanah D, Solfiyeni, Mufti HM, Maideliza T. 2025. Diversity and composition of invasive understory plants in Kapalo Banda Taram Ecotourism Area, West Sumatra, Indonesia. Biodiversitas 26: 4500-4510. Invasive plants are species that establish and spread rapidly outside their natural habitats, often dominating new environments. This study aims to analyze the composition, structure, and diversity of invasive understory plants (seedlings and ground vegetation) in the Kapalo Banda Taram Ecotourism Area, Lima Puluh Kota District, West Sumatra Province, Indonesia. This study used a survey method using two transects with purposive sampling. Location 1 (transect 1) in the eastern part and Location 2 (transect 2) in the southern part of the area. The length of each transect was 50 meters, and along the transect, 25 plots measuring 2×2 meters were systematically placed on each transect. In each plot, observations were made regarding the presence of species, the number of individuals, and environmental factors. Results showed that in Location 1, there were 18 families, 26 genera, 26 species, and 1,213 individuals of understory plants, including 9 invasive families, 14 genera, 14 species, and 1,168 individuals. In Location 2, there were 9 families, 16 genera, 17 species, and 734 individuals, with 5 invasive families, 10 genera, 10 species, and 614 individuals. The dominant families in Location 1 were Melastomataceae (31.16%), Cyperaceae (28.85%), and Poaceae (28.28%), with Cyperus rotundus as the most dominant species (IVI: 43.92%). In Location 2, Asteraceae dominated (50.14%), with Chromolaena odorata as the most dominant species (IVI: 57.52%). The Shannon-Wiener diversity index (H') indicated moderate diversity, with values of 2.34 and 2.26. Canonical Correspondence Analysis (CCA) revealed that environmental factors such as light intensity, humidity, temperature, and soil pH significantly influence the distribution and dominance of invasive understory species. This study provides valuable insights into the management of invasive plants in the Kapalo Banda Taram Ecotourism Area, aiding conservation and sustainable tourism efforts.